How Value Network-Based Co-Inovation Contribute in Competitive Advantage - Maryono, Maryono; Ghozali, Imam; Kusumawardhani, Amie; Prabantariksa, Mahelan (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2019)
This study aims to develop a comprehensive integrated model which helps in explaining the impact of value chain integration’s (VCI)’s and relational capability impact on co-innovation in a network and competitive advantage. It also explores the role of value network-based co-innovation as a mediator in the relationship between supply chain integration and competitive advantage, and in the relationship between relational capabilities and competitive advantage of a housing bank sector. The study suggests that firm gains competitive advantage by utilizing value chain integration and relational capability. It is argued here that co-innovation based on value network has mediating role to create competitive advantage. The paper provides a discussion and implication on where value lies and how value is co-created in network of interdependent relationship and illustrate this by sketching a value map in network relationship and possible innovations that can be co-created in housing bank ecosystem. The study involved a single government owned bank located in different cities, therefore the results should be generalized cautiously. This paper constitutes an attempt to stimulate efforts and provide directions on the further conceptual development of value network-based co-innovation (VNBC). The newly developed measure of VNBC and CA exempt from past conceptual streams of the determinant of CA, could be used for valid measurements in future empirical studies in the field of strategic management. The paper provides a practical implications for managers to identify value and utilize new way of analyzing value-chain to create co-innovation within housing bank ecosystem. It also allows manager to practicing relational capability which gives the most impact to competitive advantage..